2017
DOI: 10.1016/j.ica.2017.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Probing the limits of supramolecular G-quadruplexes using atomistic molecular dynamics simulations

Abstract: Guanosine and related derivatives self-assemble in the presence of cations like potassium into supramolecular G-quadruplexes (SGQs), where four guanine moieties form planar tetrads (T) that coaxially stack into columnar aggregates with broad size distributions. However, SGQs made from 8-aryl-2’-deoxyguanosine derivatives (8ArGs), form mostly octamers, or two-tetrad (2T)-SGQs, while some form dodecamers (3T-SGQs), or hexadecamers (4T-SGQs), and none reported to date form higher assemblies. A theoretical model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Earlier, we established that assembling G-derivatives is a crucial step in creating the SHS particles. , Specifically, G-derivatives containing a meta-phenyl carbonyl group attached to the C8 of the guanine moiety form SGQs containing 16 subunits (i.e., hexadecamers). , We have also shown that combining two types of G-derivatives could lead to the formation of heteromeric SGQs whose responsive properties could be modulated . Building on this, we hypothesized that combining varying proportions of 2 with 3 or 4 would enable adjusting the apparent affinity of the resulting SHS particle toward the target protein AVI .…”
Section: Resultsmentioning
confidence: 95%
“…Earlier, we established that assembling G-derivatives is a crucial step in creating the SHS particles. , Specifically, G-derivatives containing a meta-phenyl carbonyl group attached to the C8 of the guanine moiety form SGQs containing 16 subunits (i.e., hexadecamers). , We have also shown that combining two types of G-derivatives could lead to the formation of heteromeric SGQs whose responsive properties could be modulated . Building on this, we hypothesized that combining varying proportions of 2 with 3 or 4 would enable adjusting the apparent affinity of the resulting SHS particle toward the target protein AVI .…”
Section: Resultsmentioning
confidence: 95%
“…10,34 Specifically, G-derivatives containing a meta-phenyl carbonyl group attached to the C8 of the guanine moiety form SGQs containing 16 subunits (i.e., hexadecamers). 19,35 We have also shown that combining two types of G-derivatives could lead to the formation of heteromeric SGQs whose responsive properties could be modulated. 34 Building on this, we hypothesized that combining varying proportions of 2 with 3 or 4 would enable adjusting the apparent affinity of the resulting SHS particle towards the target protein AVI.…”
Section: Modulation Of Protein Affinity Via Heteromeric Shs Particlesmentioning
confidence: 89%
“…Our previous research has demonstrated that G-derivatives containing a metaphenylcarbonyl group attached to the C8 of the guanine moiety form hexadecameric SGQs, containing 16 subunits. 33,34 Therefore, we anticipated that combining 2 with 3 or 4 would lead to the formation of similar hexadecameric SGQs. Our hypothesis was supported by the presence of two sets of peaks in the 1 H NMR of homomeric assembly of SGQ2, which are more clearly visible in the signature N1H region (13-11 ppm; see Figure S44B).…”
Section: Modulation Of Protein Affinity Via Heteromeric Shs Particlesmentioning
confidence: 99%